The GNSS NavAer INCT Project Overview and Main Results - Monico, João Francisco Galera [UNESP]; de Paula, Eurico Rodrigues; Moraes, Alison de Oliveira; Costa, Emanoel; Shimabukuro, Milton Hirokazu [UNESP]; Alves, Daniele Barroca Marra [UNESP]; de Souza, Jonas Rodrigues; Camargo, Paulo de Oliveira [UNESP]; Prol, Fabricio Dos Santos; Vani, Bruno César; Pereira, Vinicius Stuani Amadeo; Junior, Paulo Sergio de Oliveira; et al. (FapUNIFESP (SciELO), 2022)
Air navigation is increasingly dependent on the use of Global Navigation Satellite Systems (GNSS). It allows the determination of the aircraft’s position in all phases of the flight and brings many advantages. Although GNSS navigation results in gains, the radio signals from these systems are strongly influenced by the ionospheric environment. It introduces errors that can affect the accuracy, integrity, availability and continuity requirements established by the International Civil Aviation Organization (ICAO). The ionospheric layer has different behaviors depending on the latitude, time of day, season of the year, geomagnetic activity and solar cycle. Since Brazil is located in a region of low latitudes, it experiences a series of unique challenges when compared to regions of mid-latitudes. For this reason, the application of GNSS-based technologies in aviation over the Brazilian territory requires an in-depth assessment of the ionosphere effects. Therefore, the Instituto Nacional de Ciência e Tecnologia (INCT) named GNSS Technology for Supporting Air Navigation was formed in 2017 to better assess the ionosphere impacts and assist government agencies and companies in the development of safe air navigation procedures over Brazil in a near future. This paper presents the most relevant advances achieved so far within this multidisciplinary project that involves Brazilian research centers and universities.
Keywords: Augmentation Systems; Ionospheric Weather over Low Latitudes; Satellite Navigation